归芪益元膏对12C6+束辐射损伤模型大鼠旁效应的影响 - Jian-qing LIANG; Jin-tian, LI; LI, Juan; Yong-qi, LIU; Xing-yao, LIN; Feng-yan, LIU; Yao-rong, AN; Xiao-wei, LI; Zi-tong, ZHANG (Jie fang jun yi xue za zhi, 2017)
Objective To investigate the bystander effect injury to lung-heart-liver-spleen caused by 12C6+ beam radiation, and explore the prevention and treatment effect of Guiqiyiyuan ointment on the injury and its mechanism. Methods Ninety healthy male Wistar rats were randomly divided into 3 groups: NC group (normal control, normal saline 2ml/kg, n=30), SR group (simple radiation, 8Gy, 2ml/kg, n=30), GO group (Guiqiyiyuan ointment 11.83g/kg, radiation, 8Gy, n=30). All the rats received intragastric administration for 7 days. The right side of the lung was modeled by 12C6+ beam radiation. After modeling, the rats were killed at 48h. The heart, liver and spleen were taken. The malonaldehyde (MDA), glutathione (GSH), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) contents were measured by colorimetry, DNA methylation rate was assayed by ELISA, and the expressions of Dnmt1, Dnmt3a and Dnmt3b were detected by immunohistochemistry. Results Compared with NC group, the contents of SOD, GSH and GSH-Px decreased